The Role of Digital Media as A Technological Innovation in Improving the Quality of Learning - Rabbani, Muzhaffar Aiman; Hamdan, Nurul Majeedah; Almasi, Mustapha (STKIP Pesisir Selatan, 2025)
The development of information technology in the industrial revolution 4.0 era has significantly transformed Islamic religious education in higher education. Digital media has become a new ecosystem that enables students to access Islamic knowledge widely, interactively, and flexibly, while also enhancing their motivation and religious insight. This is where the role of digital media integration in education becomes crucial, not merely introducing technology but also guiding students to use digital media wisely and proportionally to deepen their religious understanding This study employed a descriptive qualitative approach with Islamic Education students selected through purposive sampling, using interviews, observations, and documentation analyzed through Miles & Huberman’s model with triangulation for validity. The findings indicate that integrating digital media positively contributes to students’ religious understanding, although challenges remain, such as low digital literacy, the spread of unverified content, lecturers, limited technological skills, and the risk of digital distraction. Therefore, the role of lecturers and institutions is crucial in providing guidance, curating reliable content, and strengthening digital literacy so that digital media integration becomes an effective strategy to bridge Islamic values with the needs of the modern generation.